Quasi-Synchronous Accumulation of Apparent Oxygen Utilization and Inorganic Carbon in the South Yellow Sea Cold Water Mass From Spring to Autumn: The Acidification Effect and Roles of Community Metabolic Processes, Water Mixing, and Spring Thermal State - Yu, Si-qing; Xiong, Tian-qi; Zhai, Wei-dong (Frontiers in Marine Science, 2022)
To better understand seasonal acidification in the South Yellow Sea (SYS), four field surveys conducted in 2019 and the historical data obtained in 2018 were incorporated in this study. The lowest aragonite saturation state (Ωarag) value of 1.15 was observed in the central SYS in late autumn. Despite interannual variations in the rate of net community respiration, the quasi-synchronous accumulation of apparent oxygen utilization and excess dissolved inorganic carbon (DIC) relative to the air equilibrium were revealed in the SYS cold water mass (SYSCWM) from late spring to autumn. Correspondingly, the two acidification indexes (Ωarag and pH) decreased in logarithmic forms in the SYSCWM in warm seasons. To examine the potential influences of hydrological dynamics on seasonal acidification in the SYSCWM, a three-endmember water-mixing model was applied. The results showed that the cumulative effect of various non-conservative processes on DIC was comparable with the excess DIC relative to the air equilibrium. This implied that the summer and autumn carbonate dynamics and the acidification status of the cold water mass were almost free from the potential impacts of the weak water mixing and internal circulation in summer and autumn in a given year. The Yellow Sea Warm Current carries oceanic DIC into the SYS only in winter and early spring. This study also showed that the re-equilibrium with atmospheric CO2 at given temperature in early spring determined the initial Ωarag of the SYS before Ωarag declining in late spring, summer, and autumn. The sensitivity of coastal Ωarag changes to DIC addition is subject to both spatial and temporal variations.